Implementation Of Independent Curriculum In The Subjects Of Islamic Religious Education And Morals Education - Masruri; Waliah (Master of Islamic Studies Masters Program in the Postgraduate Institute of Islamic Studies Sultan Muhammad Syafiuddin Sambas, Indonesia, 2023)
This study aims to obtain a clear and detailed description of the planning for the Implementation of the Independent Curriculum in Islamic Religious Education Subjects and Characteristics, the Steps for Learning Islamic Religious Education and Specificities Based on the Independent Curriculum, and the Constraints faced by teachers of Islamic Religious Education and Distinctiveness in implementing an independent curriculum and its solutions. This study uses qualitative research with a descriptive approach. Data collection procedures include observation techniques, interviews, and documentation. Researchers interviewed the Principal of SMA Negeri 1 Kelam Permai, the Deputy Head of the School for Curriculum, Teachers of Islamic Religious Education and Characteristics, and representatives of Muslim students in Class X and Class XI directly. The data analysis technique uses the Miles and Huberman model with four stages: data collection, reduction, display, and verification. Data validity uses three criteria: triangulation, member checks, and increased persistence. The results of the study stated that the independent curriculum implementation plan carried out by SMA Negeri 1 Kelam Permai was good by collaborating involving various competent parties by maximizing the school's potential and resources, the learning steps carried out by teachers of religion and Islamic morals were perfect and systematically, starting from analyzing learning outcomes, and the obstacles faced by Islamic religious and moral education teachers who are less active in participating in the learning process in class, textbooks that do not meet quotas, the difficulty of controlling students in using mobile phones to support the learning process, the teacher's lack of understanding of the curriculum independent, challenges in designing differentiated learning and difficulties in making teaching modules that suit the abilities and interests of students